Multiplex nested polymerase chain reaction for Treponema pallidum using blood is more sensitive than using serum - Effendi, Ida; Rosana, Yeva; Yasmon, Andi; Indriatmi, Wresti (Faculty of Medicine, Trisakti University, 2018)
BackgroundSyphilis is a multistage disease transmitted primarily through sexual intercourse. Nowadays, the polymerase chain reaction (PCR) test for Treponema pallidum has been widely used and is expected to overcome problems in diagnostic tests for syphilis. The Treponema pallidum PCR is influenced by type of specimens, PCR methods and target genes. This study aimed to assess the use of blood and serum in multiplex nested PCR for Treponema pallidum, targeting the 23S rRNA.MethodsA cross-sectional study was conducted from April 2015 - April 2016. Sampling was carried out consecutively among patients with clinical features of secondary syphilis who came to Sexually Transmitted Disease (STD) clinics in Jakarta. All sera were also tested with Rapid Plasma Reagin (RPR) and Treponema pallidum Hemagglutination Assay (TPHA) assay, which was considered as the gold standard for this study. We determined the sensitivity and specificity of the multiplex nested PCR for Treponema pallidum using blood and serum.ResultsPCR test was performed on 122 clinical specimens (61 blood and 61 serum). The positive results of PCR test on blood was 22.95% and serum was 6.56%, while the positive results of serology was 68.85%. The sensitivity of Treponema pallidum multiplex nested PCR on blood was 30.95% compared to serum 9.52% (p=0.006). PCR test on blood is able to detect 3.25 times higher than serum. ConclusionThe use of blood has a higher proportion of positives compared to serum in Treponema pallidum multiplex nested PCR using 23S rRNA target gene.